Ovarian cancer incidence and survival in Korea: 1993–2002. Issue 3 (1st May 2007) - Chung, H. H.; Hwang, S. Y.; Jung, K. W.; Won, Y. J.; Shin, H. R.; Kim, J. W.; Lee, H. P.; ,
Abstract : This study examined incidence rates, histologic and stage distribution, and long-term survival rates of patients with ovarian cancer in Korea. A total of 11, 404 patients diagnosed with ovarian cancer between 1993 and 2002 were reported to the Korea Central Cancer Registry and the Gynecologic Oncology Committee of Korean Society of Obstetrics and Gynecology. All rates were expressed per 100, 000. The age-standardized incidence rates were 3.79 and 4.74 per 100, 000 women in 1993 and 2002, respectively. The incidence rates of ovary cancer increased with age in Korea, and over half of the patients were in the stage IA (24.8%) and IIIC (26.8%) in this study. The 5-year relative survival rate was 59.6%. Relative survivals according to the stage of FIGO at 5 years were 91.1%, 75.2%, 46.4%, and 21.2% for stages I, II, III, and IV, respectively. The 5-year relative survivals of germ cell tumors and epithelial ovarian cancer were 89.0% and 58.3%, respectively. Surgical stage and histology were the most important prognostic factors of ovarian cancer. However, the 5-year survival rate of FIGO stage IC was significantly higher than that of stage IB.